Musculoskeletal pain among dental personnel - Ismail, Ahmad Faisal; Hamshah, Arbaatul Arroshikin Nazirah; Sukmasari, Susi (Lambert Academic Publishing, 2017)
Inflammatory and degenerative conditions that affect the muscles, tendons, ligaments, joints, peripheral nerves and supporting blood vessels are known as musculoskeletal disorders (MSDs). Dental personnel’s have an increased risk of developing musculoskeletal disorders because of high workload, long working duration, involvement of repetitive movement and others. Inconvenient position and repetitive task such during treatment contribute significantly to both, musculoskeletal disorders (MSDs) and psychological stress, and finally causes fatigue. It is reported that the prevalence of musculoskeletal disorder among dental personnel are high, coupled with high demands on visualization and precision on the narrow working area. This book will assess and evaluate the prevalence and associated risk factors for MSDs among dental personnel.